1992
DOI: 10.1111/j.1365-2419.1992.tb00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental influences on the recruitment of Newfoundland/Labrador Cod*

Abstract: This paper investigates possible linkages between the environment and year‐class success of Newfoundland/ Labrador cod. Aspects of the physical environment relevant to recruitment are reviewed and the current knowledge of the patterns of spawning and larval occurrence is summarized. A critical review of investigations aimed at correlating recruitment with climactic fluctuations is made and concludes that these studies have been largely fruitless. A series of numerical simulations of particle drift are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
1
30
1
Order By: Relevance
“…It may have taken several years of this distributional shift to have a significant effect on population biomass. Helbig et al (1992) and Hutchings et al (1993) suggested that deep spawning habits would be detrimental to recruitment since the currents over deeper water would tend to transport the larvae away from the shelf and thus reduce survival. The present study provides further evidence that spawning concentrations during the 1980s and 1990s did change their distribution and behaviour significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It may have taken several years of this distributional shift to have a significant effect on population biomass. Helbig et al (1992) and Hutchings et al (1993) suggested that deep spawning habits would be detrimental to recruitment since the currents over deeper water would tend to transport the larvae away from the shelf and thus reduce survival. The present study provides further evidence that spawning concentrations during the 1980s and 1990s did change their distribution and behaviour significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Their data from deeper waters may not have been adequate to reflect the extent of the spawning distribution along the edge of the north-east Newfoundland Shelf, and so the spawning distribution that we observed during the 1980s and 1990s may have been quite different from earlier years. Helbig et al (1992), using numerical simulations of particle drift, suggested that reproductive activity of cod on the Labrador Shelf is separate from that of the Grand Banks. It is entirely possible that the spawning behaviour and distributions of the two areas are quite different, with the Labrador component occurring along the edge.…”
Section: Resultsmentioning
confidence: 99%
“…and larval drift (Helbig et al 1992) and adult movements between spawning and feeding areas (Rose 1993). Such cod groups have diverse population sizes and ranges.…”
Section: Atlantic Cod Migrations D Robichaud and G A Rosementioning
confidence: 99%
“…Recruitment at ages 3 and 4 fluctuated by a factor of 9 during the 30-year period from 1962 to 1987 (Baird et al, 1991). A number of hypotheses explored to explain recruitment in northern cod include salinity, temperature, dispersal of eggs and larvae, and shifts in spawning location affecting egg dispersal and survival (Sutcliffe et al, 1983;Helbig et al, 1992;Myers et al, 1993;deYoung and Rose, 1993). These hypotheses have focused exclusively on the egg and larval stages prior to the juvenile stages, and the results have been largely inconclusive.…”
Section: Introductionmentioning
confidence: 98%